Social capital in successful sustainable rural development enterprises - Román Arredondo, Patricia; Hernández Juárez, Martín; León Merino, Aurelio; Sangerman- Jarquín, Dora María (Revista Mexicana de Ciencias Agrícolas, 2017)
Rural enterprises are entities that contribute to the generation of jobs and income in the rural sector. To this end, rural families have developed various community- based initiatives to better leverage their limited resources or to efficiently link to different levels of structures and processes individually and collectively to operate successfully. However, there are studies that indicate that more than half of the start-up companies have not had the expected success and tend to disappear (World Bank, 2007), which is due to factors related to deficiencies in the organization, limitations in interpersonal relationships, internal conflicts and mistrust among others (Acuña, 2011; Toiber, 2016; Díaz et al ., 2016). The objective of this research was to identify the role of social capital elements as well as the material and non-material benefits derived from this operation process of the companies of the Red Nacional de Desarrollo Rural Sustentable (RENDRUS). The research was conducted in 2016, with a mixed approach, data were obtained from a survey and open interview applied to 20 RENDRUS representatives. The results show that the existence of social capital allows companies to obtain various material and non-material benefits that positively influence their success.